2017
DOI: 10.1186/s41043-017-0100-6
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and poor oral health status are major risks among primary school children at Lasbela, Balochistan, Pakistan

Abstract: BackgroundThis survey was focusing on health and oral hygiene status of primary school children at Lasbela district considering the comparatively less developed and socio demographically deprived part of the Country.MethodsA cross sectional survey was conducted to determine the health status of primary school children in seven tehseels of district Lasbela, Balochistan after applying proportionate sampling technique from March 2015 to July 2015. Field teams visited assigned schools to screen children and collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Though multiple factors are associated with malnutrition, poor hygiene practice is one of the major factors linked to malnutrition among the school age children 11, 12. Nutritional status of children in many developing countries is affected by hygiene status, such as lack of clean water, poor sanitation, poor hygiene practices, and lack of access to toilets 13.…”
mentioning
confidence: 99%
“…Though multiple factors are associated with malnutrition, poor hygiene practice is one of the major factors linked to malnutrition among the school age children 11, 12. Nutritional status of children in many developing countries is affected by hygiene status, such as lack of clean water, poor sanitation, poor hygiene practices, and lack of access to toilets 13.…”
mentioning
confidence: 99%
“…Twenty-eight studies reported data specifically on children between 5 and 15 years of age ( 19 , 21 – 23 , 25 – 29 , 31 , 32 , 35 , 38 , 44 , 45 , 47 – 50 , 52 , 54 , 55 , 59 , 60 , 62 – 64 , 67 ). The remaining 23 studies had children in our age group of interest but beyond it too, with seven reporting data on children between 0 and 19 years of age ( 24 , 34 , 51 , 56 , 58 , 61 , 65 ) and 16 reporting on children 5 and 19 years of age ( 18 , 20 , 30 , 33 , 36 , 37 , 39 – 43 , 46 , 53 , 57 , 66 , 68 ). There were only five studies that reported data specifically on children in the 5 to 10 age group ( 29 , 34 , 64 – 66 ) and only three studies in the 10 to 15 years age group ( 21 , 24 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were only five studies that reported data specifically on children in the 5 to 10 age group ( 29 , 34 , 64 – 66 ) and only three studies in the 10 to 15 years age group ( 21 , 24 , 47 ). Province wise; 20 studies were conducted in Punjab ( 19 , 22 , 24 , 28 , 29 , 31 , 39 , 40 , 44 , 46 , 52 – 54 , 58 , 65 , 67 ), 15 in Sindh ( 18 , 20 , 21 , 23 , 30 , 32 , 36 – 38 , 43 , 45 , 49 , 55 , 63 ), eight in Khyber Pakhtoonkhwa (KP) ( 26 , 34 , 35 , 47 , 48 , 50 , 61 , 64 ), two in Balochistan ( 25 , 51 ), four from the federal capital ( 27 , 42 , 66 , 68 ), and three from multiple cities across Pakistan ( 41 , 56 , 57 ). The remaining three studies failed to report their location ( 33 , 59 , 62 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal dietary intake was rarely observed among the study subjects while protein-calorie malnutrition and vitamin deficiency was common among a large proportion of the sample ( Table 2). According to world health statistics, globally 186 million children are presented with stunted growth while 20 million cases of acute malnutrition are observed 21 .…”
Section: Discussionmentioning
confidence: 99%